Теплова стійкість поверхонь деталей внаслідок вібраційно-відцентрового зміцнення - Кирилів, Ярослав (КІНПАТРІ ЛТД, 2013)
The report deals with investigation on the heat stability of a friction surface obtained by means of vibration and centrifugal strengthening (VCS) on 40X steel. The maximum temperature value, for which physical, mechanical and service properties are preserved, is defined.
Thermal stability of friction surface as a result of vibration-centrifugal strengthening